ROSCAs THROUGH THE ISLAMIC COMMUNITY: AN ALTERNATIVE TO ENHANCING ENTREPRENEURSHIP AND WEALTH - Pambekti, Galuh Tri; Yusfiarto, Rizaldi; Nugraha, Septy Setia (Bank Indonesia, 2022)
The purpose of the study is to analyse the influence of the motives and benefits of participation in Rotating Savings and Credit Associations (ROSCAs) on household wealth and entrepreneurship through mediating community commitment. Structural equation modeling (SEM) was used on the data collected using purposive sampling and a sample of 225 respondents in the provinces of East Java, Central Java, West Java, D.I. Yogyakarta, and D.K.I. Jakarta. The results show that ROSCAs have a direct effect on entrepreneurial intention and may affect household wealth. It is also concluded that ROSCAs can be an instrument of Islamic social finance, as their characteristics are not burdensome to members. They involve the principle of cooperation, and are not affected by interest rates or inflation. Acknowledgment The authors would like to thank Bank Indonesia Institute, Bank Indonesia, for the funding that made this study possible.